Skills Development for Graduate Employability in Bangladesh: Japanese Language in TVET Program - Alam, Md Jahangir; Sharmin, Dilruba (Journal of Technical Education and Training, 2023)
The tremendous potential of Technical and Vocational Education and Training (TVET) appears evident worldwide, including in Bangladesh, where the emphasis is primarily on individual skills development for decent employment. Numerous studies have demonstrated that varying degrees of development of soft skills and hard skills contribute to the strength and capability of human capital. It is well acknowledged that knowledge and technology are rapidly updated in the contemporary world. This study explores how skills development influences sustainable employability through the lens of the Japanese language skills development program in TVET. Moreover, this research aims to study the impact of Japanese language programs in Bangladesh's TVET system on skills development and sustainable employability. It aims to assess how the skills acquired through these programs benefit both the domestic and international job markets related to Japanese language abilities. This research employs a mixed-methods research approach examining the participants’ perceptions and understandings of those TVET students who have enrolled or graduated from the Japanese language program. The research endeavours to conduct a theoretical examination of the human capital development theory and to establish a connection between the Japanese language program and its associated approach, knowledge, and method. By examining the research findings, this study found that the TVETs’ Japanese language program significantly positively impacts individuals’ hard and soft skills development, improving the quality and form of employability, increasing individual wages, and playing a supportable role in achieving the SDG 8 of decent work and economic growth. Several practical initiatives have been recommended to increase this language program’s sustainability in TVET.